Ce-Ti bimetallic oxide modified chitosan composite material as well as preparation method and application thereof

The preparation of enzyme-imitated catalytic sensors through Ce-Ti bimetal oxide modified chitosan composite material solves the cost and complex operation problems of the detection of S2− and CrO42− in the prior art, and achieves fast and efficient visibility Detection effect.

CN119158621APending Publication Date: 2024-12-20QUFU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411156839.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to detect S2− and CrO42− quickly and efficiently in the field, requiring expensive analytical instruments and skilled operators.

Method used

Provide a composite material of Ce-Ti bimetal oxide modified chitosan, which is coupled with carboxylated chitosan through coordination bonds to form a nanofiber structure, and is used to prepare enzyme-like catalytic sensors to achieve S2− and CrO42 −Visibility detection.

Benefits of technology

The specific detection of S2− and CrO42− is realized, which simplifies the detection process, reduces operational complexity and equipment costs, and meets the needs of fast and efficient field detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158621A_ABST
    Figure CN119158621A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a Ce-Ti bimetal oxide modified chitosan composite material and a preparation method and application thereof.The composite material comprises carboxylated chitosan and nano-metal composite oxide loaded on the surface of the carboxylated chitosan, the nano-metal composite oxide is coupled with groups on the carboxylated chitosan through coordinate bonds, and the Ce-Ti bimetal oxide modified chitosan composite material is obtained. The nanometer metal composite oxide comprises nanometer cerium dioxide, titanium dioxide and cerium titanium oxide, the composite material forms a nanometer fiber shape, and the composite material recognizes good specificity and selectivity of S2 and CrO42 through contrast colors, so that trace S2 and CrO42 in environmental water, food and medicine samples can be conveniently, efficiently and visually detected; complex detection steps are not needed, large-scale analysis instruments are not needed, operation is easier, and the requirements for rapid, efficient and field instant detection can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanozymes and catalytic sensing applications, and more specifically, to a composite material of Ce-Ti bimetallic oxide modified chitosan and a preparation method and application thereof. Background Art

[0002] S 2− and CrO4 2− There are two common and highly toxic anions. 2− It is widely distributed in daily cosmetics, landfills and industrial wastewater. Once absorbed by the human body, it can cause a series of chronic diseases such as diabetes, Alzheimer's disease, cirrhosis, Down syndrome, etc. Therefore, the World Health Organization stipulates that S in drinking water should not exceed 100 million tons. 2− The content does not exceed 0.6 mM. 2− A highly oxidizing environmental pollutant, widely found in laboratory washing liquids, factory leather preparations and metal plating, industrial pigments, and tanning, rubber and ceramic production processes; once it enters the human body, it has a strong irritating and corrosive effect on the respiratory and digestive systems, and can cause allergic dermatitis or eczema, pharyngitis, rhinitis, tuberculosis, bronchitis, diarrhea, abdominal discomfort and diarrhea and other poisoning symptoms. 2− and CrO4 2− The methods include atomic absorption spectroscopy, fluorescence spectroscopy, electrochemistry, high performance liquid chromatography, inductively coupled plasma mass spectrometry and colorimetric analysis, which are effective in preventing and controlling S 2− and CrO4 2− However, most of the above methods require expensive analytical instruments and skilled operators, which cannot meet the needs of fast, efficient and instant field detection. Summary of the invention

[0003] The present application is provided to solve the above-mentioned defects existing in the prior art. It is necessary to provide a composite material of Ce-Ti bimetallic oxide modified chitosan and its preparation method and application, to provide a composite material with nanozyme performance, which is more convenient to use and can solve the problem of S 2− and CrO4 2− The detection of these problems requires expensive analytical instruments and skilled operating technicians.

[0004] In the first aspect of the present application, a composite material of Ce-Ti bimetallic oxide modified chitosan is provided, wherein the composite material comprises carboxylated chitosan and nano-metal composite oxide loaded on the carboxylated chitosan fiber, wherein the nano-metal composite oxide is coupled with the electron-rich N and O groups on the carboxylated chitosan through coordination bonds, wherein the nano-metal composite oxide comprises nano-cerium dioxide (CeO2), titanium dioxide (TiO2) and cerium titanium oxide (Ce2Ti2O7), and the composite material forms the shape of nanofibers.

[0005] HR-TEM showed three crystal plane spacings of 0.319 nm, 0.235 nm and 0.294 nm, which were respectively attributed to the (111) crystal plane of nano-CeO2, the (220) crystal plane of nano-TiO2 and the (112) crystal plane of nano-Ce2Ti2O7.

[0006] In some embodiments, the particle size of the nano-metal composite oxide is 4.13±0.58 nm.

[0007] In some embodiments, the molar ratio of carboxylated chitosan, Ce element, and Ti element in the composite material is 6-10:7-10:1; for example, 7:7:1, 7:8:1, 7:9:1, etc.

[0008] The second aspect of the present application provides a method for preparing a composite material of Ce-Ti bimetallic oxide modified chitosan as described in any embodiment of the present application, the preparation method comprising: mixing cerium salt, titanium salt and carboxylated chitosan solution, and then performing a reflux reaction under microwave conditions to obtain a composite material of Ce-Ti bimetallic oxide modified chitosan.

[0009] In some embodiments, a pH adjusting reagent is also added to the reaction raw materials; the pH adjusting reagent includes an aqueous ammonia solution, an aqueous sodium hydroxide solution, and the like.

[0010] In some embodiments, the mass percentage of the solute in the pH adjusting agent is 25-28%, and the volume ratio of the pH adjusting agent to the carboxylated chitosan solution is 20-30:1.

[0011] In some embodiments, the mass percentage of the solute in the carboxylated chitosan solution is 0.03-0.1 wt %. Preferably, the mass percentage of the solute in the chitosan solution is 0.05-0.06 wt %.

[0012] In some embodiments, the cerium salt may be cerium nitrate hexahydrate Ce(NO3)3·6H2O or cerium sulfate Ce2(SO4)3, etc. In some embodiments, the titanium salt may be Ti(SO4)2, etc.

[0013] In some embodiments, the reflux reaction conditions are: temperature of 100-120° C., reaction time of 10-40 min, preferably 10-30 min.

[0014] The third aspect of the present application provides a composite material of Ce-Ti bimetallic oxide modified chitosan as described in any embodiment of the present application and a method for preparing the composite material of Ce-Ti bimetallic oxide modified chitosan as described in any embodiment of the present application and their application in nanozymes.

[0015] In a fourth aspect of the present application, a composite material of Ce-Ti bimetallic oxide modified chitosan as described in any embodiment of the present application is provided as a nanozyme in S 2− and CrO4 2− Ce-Ti bimetallic oxide modified chitosan composite material for S 2− and CrO4 2− It has specific detection effect.

[0016] In a fifth aspect of the present application, an enzyme-mimicking catalytic sensor is provided, wherein the enzyme-mimicking catalytic sensor comprises the composite material of Ce-Ti bimetallic oxide-modified chitosan as described in any embodiment of the present application.

[0017] In some embodiments, the enzyme-mimicking catalytic sensor further includes TMB (3,3',5,5'-tetramethylbenzidine) and a buffer solution of disodium hydrogen phosphate-citric acid. In the air, Ti-co-Ce ox@CC can rapidly catalyze the oxidation of TMB to produce a blue color. 2− After adding, the color changes from light blue to blue, and the color changes from light to dark. CrO4 2− After addition, a hypochromic effect is shown, and the color changes from dark to light. The buffer solution provides an environment for the reaction during the detection process.

[0018] In some embodiments, the Ce-Ti bimetallic oxide modified chitosan composite material in the enzyme-mimicking catalytic sensor exists in the form of a dispersed solution, the TMB exists in the form of a solution, the volume ratio of the dispersed solution, the TMB solution and the buffer solution is 2-10:5-10:5-10, and the concentration of the dispersed solution is 0.2-0.5 mg∙mL −1 The concentration of the TMB solution is 1-3 mmol∙L −1 , the pH of the buffer solution is 2.5-3.5.

[0019] The composite material of Ce-Ti bimetallic oxide modified chitosan provided in each embodiment of the present application and its preparation method and application, the composite material comprises carboxylated chitosan and nano-metal composite oxide loaded on the surface of the carboxylated chitosan, the nano-metal composite oxide and carboxylated chitosan are coupled with the groups on the carboxylated chitosan through coordination bonds, and the combination is firm to form a stable composite material, the composite material has more oxygen vacancies and multivalent Ce and Ti, and therefore has better nanozyme mimetic enzyme catalytic activity. 2− and CrO4 2− Good specificity and selectivity facilitate efficient visual detection of trace S in environmental water, food and pharmaceutical samples 2− and CrO4 2− It does not require complicated detection steps or the use of large analytical instruments. It is easier to operate and can meet the needs of fast, efficient, and instant field detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0021] Figure 1 (A) a) shows a TEM characterization image of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; c) shows an enlarged image of the circled portion in a) (inset: HR-TEM and particle size distribution diagram); Figure 1 (B) shows a SEM image of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; FIG1 (C) shows the EDS elemental analysis spectrum of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; Figure 2 (a) shows the XRD pattern of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; Figure 2 (b) shows the FT-IR pattern of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; Figure 2 (c) shows the ζ potential pattern of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application.

[0022] Figure 3 (a) shows the wide-angle x-ray photoelectron spectrum of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; FIG3 (b) shows the Ce 3d XPS high-resolution spectrum of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; FIG3 (c) shows the Ti 2p XPS high-resolution spectrum of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application; FIG3( d ) shows the XPS high-resolution spectrum of O 1s of the Ti-co-Ce ox@CC composite material prepared in Example 1 of the present application.

[0023] Figure 4 (a) shows the UV-visible absorption spectra of CC, Ti-co-Ce oxide and Ti-co-Ce ox@CC catalytic oxidation of TMB; FIG4( b ) shows the time response curve at 652 nm corresponding to the curve in FIG4( a ); Figure 4 (c) shows the vc of TMB catalytically oxidized by Ti-co-Ce ox@CC and Ti-co-Ce oxide. TMB Comparison chart; Figure 4(d) shows the double reciprocal curve (1 / v against 1 / c) corresponding to Figure (c). TMB ); Figure 5 (a) shows the effect of common interferences on the catalytic colorimetric S of the Ti-co-Ce ox@CC-TMB system. 2− The impact of; Figure 5(b) shows the relationship between common interferents and S 2− When coexisted, Ti-co-Ce ox@CC-TMB catalyzed colorimetric detection of S 2− System A 652 The impact of Figure 5(c) shows the catalytic colorimetric detection of S 2− UV-vis spectroscopic titration curve and its corresponding color change (c S 2− From 0.0 to 1.5×10 −5 mol·L −1 ); Figure 5(d) shows ΔA 652 With c S 2− The linear relationship curve of Figure 6 (a) shows the effect of common interferences on the catalytic colorimetric CrO4 of Ti-co-Ce ox@CC-TMB system 2− The impact of Figure 6 (b) shows the relationship between common interferences and CrO42− Catalytic colorimetric detection of CrO4 by Ti-co-Ce ox@CC-TMB in the presence of 2− System A 652 The impact of Figure 6(c) shows the catalytic colorimetric detection of CrO4 2− UV-vis spectroscopic titration curve and its corresponding color change (c CrO4 2− From 0.0 to 1.2×10 −5 mol·L −1 ); Figure 6(d) shows ΔA 652 With c CrO4 2− The linear relationship curve. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.

[0025] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0026] According to an embodiment of the present application, a composite material of Ce-Ti bimetallic oxide modified chitosan is provided, wherein the composite material comprises carboxylated chitosan and nano-metal composite oxide loaded on the carboxylated chitosan fiber, wherein the nano-metal composite oxide is coupled with the electron-rich N and O groups on the carboxylated chitosan fiber through coordination bonds, wherein the nano-metal composite oxide comprises nano-cerium dioxide (CeO2), titanium dioxide (TiO2) and cerium titanium oxide (Ce2Ti2O7), and the composite material forms the shape of nanofibers.

[0027] Carboxylated chitosan is a fiber structure that provides many oxygen-rich groups, including hydroxyl, carboxyl and amino groups. Nano-metal composite oxides are coupled to the groups on carboxylated chitosan through coordination bonds and attached to the fibers of carboxylated chitosan. The interaction between carboxylated chitosan and metal oxides is the coordination force between electron-rich atoms and electron-deficient metal atoms.

[0028] The HR-TEM showed three crystal plane spacings of 0.319 nm, 0.235 nm and 0.294 nm, which were respectively attributed to the (111) crystal plane of nano-CeO2, the (220) crystal plane of nano-TiO2 and the (112) crystal plane of nano-Ce2Ti2O7. The nano-CeO2 and nano-TiO2 have strong direct interaction or mutual penetration to form a multivalent metal composite oxide.

[0029] Carboxylated chitosan and metal composite oxides cooperate with each other, and carboxylated chitosan can enhance the stability of the composite material and its dispersibility in the aqueous phase. The composite material not only has oxygen vacancies of carboxylated chitosan, but also has multivalent metal composite oxides, so it has the mimetic enzyme catalytic activity of nanozymes.

[0030] In some embodiments, the particle size of the nano-metal composite oxide is 4.13±0.58 nm.

[0031] In some embodiments, the molar ratio of carboxylated chitosan, Ce element, and Ti element in the composite material is 6-10:7-10:1; for example, 7:7:1, 7:8:1, 7:9:1; preferably, the molar ratio of Ce element to Ti element is 9: 1. The molar ratio between carboxylated chitosan, Ce element, and Ti element can make the obtained composite material have better nanozyme properties.

[0032] According to an embodiment of the present application, a method for preparing a composite material of Ce-Ti bimetallic oxide modified chitosan described in any embodiment of the present application is also provided, the preparation method comprising: mixing cerium salt, titanium salt and carboxylated chitosan solution, and then performing a reflux reaction under microwave conditions to obtain a composite material of Ce-Ti bimetallic oxide modified chitosan. During the microwave and reflux reaction process, the cerium salt and titanium salt become metal composite oxides, and the formed metal composite oxides form particles attached to the fiber surface.

[0033] Therefore, the present application provides a preparation method with mild reaction conditions, simple operation steps and low cost.

[0034] In some embodiments, a pH adjusting reagent is also added to the reaction raw materials; the pH adjusting reagent includes an aqueous ammonia solution, an aqueous sodium hydroxide solution, and the like.

[0035] In some embodiments, the mass percentage of the solute in the pH adjusting agent is 25-28%, and the volume ratio of the pH adjusting agent to the carboxylated chitosan solution is 1:20-30. For example, the volume ratio of the pH adjusting agent to the carboxylated chitosan solution is 1:25, 1:26, etc.

[0036] In some embodiments, the mass percentage of the solute of the carboxylated chitosan solution is 0.03-0.1wt%. Preferably, the mass percentage of the solute of the chitosan solution is 0.05-0.06wt%. For example, 0.05wt% or 0.06wt%. The solvent of the carboxylated chitosan solution can be water and / or ethanol. When the solvent is water and ethanol, the volume ratio of water to ethanol is 1:3-5.

[0037] In some embodiments, the cerium salt may be cerium nitrate hexahydrate Ce(NO3)3·6H2O, cerium sulfate Ce2(SO4)3, etc. In some embodiments, the titanium salt may be Ti(SO4)2, etc.

[0038] In some embodiments, the reflux reaction conditions are: temperature of 100-120° C., reaction time of 10-40 min. The preferred reaction time is 10-30 min. Selecting appropriate reaction temperature and reaction time helps the cerium salt and titanium salt to become metal composite oxides and form a fiber-shaped composite material.

[0039] After the reflux reaction is completed, the reaction mixture is centrifuged to obtain a solid; the solid is washed with water and dried to obtain a composite material of Ce-Ti bimetallic oxide modified chitosan.

[0040] According to the embodiments of the present application, a composite material of Ce-Ti bimetallic oxide modified chitosan described in any embodiment of the present application and a preparation method of a composite material of Ce-Ti bimetallic oxide modified chitosan described in any embodiment of the present application are also provided for use in nanozymes. The composite material of Ce-Ti bimetallic oxide modified chitosan was detected by XPS, confirming that the content of oxygen vacancies it had accounted for 72.4%, and contained multivalent Ce and Ti, as well as satellite peaks, so that the composite material had the mimetic enzyme catalytic activity of nanozymes.

[0041] According to the embodiments of the present application, a composite material of Ce-Ti bimetallic oxide modified chitosan described in any embodiment of the present application is provided as a nanozyme in S 2− and CrO4 2− Ce-Ti bimetallic oxide modified chitosan composite material for S 2− and CrO4 2− It has a specific detection effect. It is helpful for the detection of S in the fields of environmental water, food, medicine and health. 2− and CrO4 2− Carry out corresponding tests.

[0042] According to an embodiment of the present application, an enzyme-mimicking catalytic sensor is further provided, and the enzyme-mimicking catalytic sensor comprises the composite material of Ce-Ti bimetallic oxide-modified chitosan described in any embodiment of the present application.

[0043] In some embodiments, the enzyme-mimicking catalytic sensor further includes TMB and a buffer solution of disodium hydrogen phosphate-citric acid. In the air, Ti-co-Ce ox@CC can rapidly catalyze and oxidize TMB to produce a blue color. 2− After adding, the color changes from blue to colorless, resulting in a color reduction effect, and the color changes from dark to light. CrO4 2− After addition, a color enhancement effect occurs, which changes the color from light blue to dark blue. The buffer solution provides an environment for the reaction to occur during the detection process.

[0044] Therefore, the present application provides a method for detecting S 2− and CrO4 2− The visual sensor can detect food, water sources, etc., and is easy to operate, which improves its applicability.

[0045] In some embodiments, the Ce-Ti bimetallic oxide modified chitosan composite material in the enzyme-mimicking catalytic sensor exists in the form of a dispersed solution, the TMB exists in the form of a solution, the volume ratio of the dispersed solution, the TMB solution and the buffer solution is 2-10:5-10:5-10, and the concentration of the dispersed solution is 0.2-0.5 mg∙mL −1 The concentration of the TMB solution is 1-3 mmol∙L −1 , the pH of the buffer solution is 2.5-3.5. Preferably, the concentration of the dispersed solution is 0.34 mg∙mL −1 The concentration of the TMB solution is 1.50 mmol∙L −1 , the pH of the buffer solution = 3.0.

[0046] The composite material, TMB and buffer solution work together to form a sensor system that cooperates with each other, and then the S 2− and CrO4 2− Concentration detection.

[0047] Example 1 Weigh 0.25 g of carboxylated chitosan and disperse it into a mixed solution of 100 mL of H2O and 400 mL of ethylene glycol by ultrasonic dispersion to obtain a chitosan dispersion with a mass fraction of 0.05 wt %; In a 100 mL three-necked flask, 78.16 mg (0.18 mmol) Ce(NO3)3·6H2O, 4.80 mg (0.02 mmol) Ti(SO4)2, 50.0 mL 0.05 wt % chitosan dispersion and 2000 μL 25%~28% ammonia water were added in sequence and stirred at room temperature for 2.0 h. The three-necked flask was placed in a microwave synthesizer and refluxed at 110°C for 20 min. After the reaction system was cooled to room temperature, it was centrifuged at 6,000 r / min, washed with water 3 times, and then vacuum dried at 60°C to obtain the prepared Ti-co-Ce ox@CC nanozyme.

[0048] Comparative Example 1 In a 100 mL three-necked flask, add 78.16 mg (0.18 mmol) Ce(NO3)3·6H2O, 4.80 mg (0.02 mmol) Ti(SO4)2 and 2000 μL of 25%~28% ammonia water in sequence and stir at room temperature for 2.0 h. Place the three-necked flask in a microwave synthesizer and reflux at 110°C for 20 min. After the reaction system is cooled to room temperature, centrifuge at 6,000 r / min, wash with water 3 times, and then vacuum dry at 60°C to obtain the metal composite oxide Ti-co-Ceoxide.

[0049] Performance Characterization The structure of the Ti-co-Ce ox@CC nanozyme prepared in Example 1 was characterized by TEM, SEM, HR-TEM, EDS, XRD, FT-IR, ζ and XPS. TEM and SEM in Figures 1 (a) and 1 (b) confirm that the morphology of Ti-co-Ce ox@CC is fibrous; further magnification shows in Figure 1 (c) that the Ti-co-Ce ox@CC fibers are composed of Ti-co-Ce bimetallic oxide particles with a particle size of 4.13±0.58 nm; EDS in Figure 1 (d) proves that Ti-co-Ce ox@CC contains Ti, Ce, N, C and O elements, and the molar ratio of Ce to Ti is 9:1, which is consistent with its feed ratio; the HR-TEM in the inset of Figure 1 (c) contains three crystal plane spacings of 0.319 nm, 0.235 nm and 0.294 nm, which belong to the (111) crystal plane of nano-CeO2, the (220) crystal plane of nano-TiO2 and the (112) crystal plane of nano-Ce2Ti2O7, respectively. Ti-co-Ce ox@CC fibers not only contain nano-CeO2 and nano-TiO2, but the two also have strong interaction or mutual penetration.

[0050] The XRD pattern in Figure 2 (a) demonstrates the crystal phase and crystallinity of the prepared Ti-co-Ce ox@CC nanozyme. 2θ=28.55 o , 47.16 o and 76.90 o The XRD peaks at are attributed to the (111), (220) and (331) crystal planes of nano-CeO2 (JCPDScard No. 04-0593); 2θ = 56.81 o and 65.82 o The XRD peaks are attributed to the (220) and (221) crystal planes of nano-TiO2 (JCPDS card No. 89-8304). From the FT-IR of Figure 2 (b), it can be concluded that the isolated chitosan (CC curve of Figure 2 (b)) has peaks at 3427, 1654, 1568 and 1065 cm −1 The FT-IR peaks are attributed to the stretching vibrations of OH(NH), C=O, CN, and CO bonds. In Ti-co-Ce ox@CC, the above FT-IR peaks all appear but shift to 3411, 1636, 1552, and 1071 cm, respectively. −1 , indicating that the OH(NH), C=O, CN and CO bonds of nano-Ti-co-Ce oxide and carboxylated chitosan have strong coordination effects, which makes it have high stability. This stability can be further confirmed by the ζ-potential of Figure 2 (c): the ζ-potential of nano-Ti-co-Ce oxide alone is only -11.79 mV, while the ζ-potential of Ti-co-Ce ox@CC is -37.05 mV. That is, the introduction of carboxylated chitosan greatly enhances the stability of Ti-co-Ce ox@CC nanoenzyme and its dispersibility in water phase.

[0051] The X-ray photoelectron wide-angle spectrum in Figure 3 (a) further confirms that the prepared Ti-co-Ce ox@CC contains all the feed elements Ti, Ce, N, C and O. In the high-resolution XPS spectrum of Ce 3d in Figure 3 (b), the six XPS peaks at 881.30, 885.20, 898.20, 900.27, 903.74 and 916.32 eV are respectively attributed to Ce 3+ 3d 5 / 2 、Ce 3d 5 / 2 Satellite peak, Ce 4+ 3d 5 / 2 、Ce 3+ 3d 3 / 2 、Ce 3d 3 / 2 Satellite peaks and Ce 4+ 3d 3 / 2; In the Ti 2p high-resolution XPS spectrum of Figure 3 (c), the XPS peaks at 457.85, 458.50, 463.30 eV and 464.70 eV are respectively attributed to Ti 3+ 2p 3 / 2 、Ti 4+ 2p 3 / 2 、Ti 3+ 2p 1 / 2 and Ti 4+ 2p 1 / 2 In the high-resolution XPS spectrum of O1s in Figure 3 (d), the XPS peaks at 529.20, 531.37, and 532.86 eV are respectively attributed to lattice oxygen (O L ), surface hydroxyl oxygen (O ―OH ) and adsorbed oxygen (O S ), the content of oxygen vacancies accounts for 72.4%. Multivalent Ce and Ti, satellite peaks and higher oxygen vacancy content will help improve the mimetic enzyme catalytic activity of the prepared Ti-co-Ce ox@CC nanozyme.

[0052] Figure 4 shows the UV spectrum and enzyme catalytic activity of the prepared Ti-co-Ce ox@CC nano-mimetic enzyme components that synergistically enhance the simulated oxidase activity. In Figure 4 (a), the CC curve represents chitosan, and the Ti-co-Ce oxide curve represents the single nano-metal composite oxide (including nano-cerium dioxide, titanium dioxide and cerium titanium oxide) prepared in Comparative Example 1. It can be seen from Figure 4 (a) that Ti-co-Ce ox@CC can quickly catalyze the oxidation of TMB in the air, showing the largest A in all test systems. 652 and the darkest blue; from A in Figure 4(b) 652 -The time response curve shows that within 600 s, the A of the Ti-co-Ce ox@CC catalytic oxidation TMB system 652 The initial value, maximum value and growth rate of Ti-co-Ce ox@CC are also the largest in all test systems; the above results show that the components of Ti-co-Ce ox@CC have good synergistic enhancement of enzyme-like catalytic activity. Figure 4 (c) and Figure 4 (d) are the vc of TMB catalyzed by Ti-co-Ce ox@CC and Ti-co-Ce oxide, respectively. TMB Comparison chart and corresponding double reciprocal curve (1 / v against 1 / c TMB ) comparison chart; From Figure 4 (c) and Figure 4 (d), it can be seen that the kinetic parameters (Vmax / Km) of the catalytic oxidation of TMB by Ti-co-Ce ox@CC and Ti-co-Ce oxide are 6.67×10 −8 M.s −1 / 0.0178 mM and 4.31×10−8 M.s −1 / 0.0471 mM, further confirming the good synergistic enhancement of enzyme-like catalytic activity among Ti-co-Ce ox@CC components.

[0053] Example 2 (1) Preparation of Ti-co-Ce ox@CC standard solution: The prepared Ti-co-Ce ox@CC material was ultrasonically dispersed in double distilled water to a concentration of 0.34 mg∙mL −1 The Ti-co-Ce ox@CC standard solution was stored at room temperature for future use.

[0054] (2) Preparation of TMB standard solution Weigh 36 mg (1.5 mmol) 3,3',5,5'-tetramethylbenzidine (TMB) and dissolve it in a mixture of 100.0 mL double distilled water and 100 mL DMSO to prepare a 1.5 mM TMB standard solution. Store it at room temperature and dilute it to the required concentration when using it.

[0055] (3) Take 6.0 mL (0.34 mg∙mL −1 ) Ti-co-Ce ox@CC standard dispersion, 8.0 mL (1.50mmol∙L −1 ) TMB and 8.0 mL (pH = 3.0) Na2HPO4-citric buffer solution were placed in a 50 mL dry round-bottom flask to obtain a Ti-co-Ce ox@CC-TMB mixed solution, which was aged at room temperature for 35 min and set aside.

[0056] Experimental example (1) S 2− and CrO4 2− Preparation of standard solution Weigh 0.78 mg (0.01 mmol) sodium sulfide and 1.62 mg (0.01 mmol) sodium chromate, respectively, and dissolve them in a mixture of 100.0 mL double distilled water and 100 mL DMSO to prepare a 10.0 mM S 2− and 10.0 mM CrO4 2− The standard solution should be stored at room temperature and diluted to the required concentration before use.

[0057] (2) Preparation of environmental test samples: 100.0 mL of surface water samples including tap water, Yihe River water and Liaohe River water were randomly measured and filtered three times with a microporous filter membrane with a pore size of 0.22 μm and stored at room temperature for later use.

[0058] 5 g of fresh pork was randomly weighed and placed in a juicer containing 100 mL of H2O for stirring for 20 min. After being left in the air at room temperature for decay, it was centrifuged at 7000 r / min for 15 min. The supernatant was then filtered through a 0.22 μm microporous filter membrane and used immediately.

[0059] Randomly measure 10 mL of fresh milk, leave it in the air at room temperature until it spoils, centrifuge it at 7000 r / min for 15 min, and filter the supernatant through a 0.22 μm microporous filter membrane for immediate use.

[0060] Collect 20 mL of chromic acid washing solution discarded in the laboratory, centrifuge it at 8000 r / min for 10 min, dilute the supernatant 100 times with pure water, and store it at room temperature for later use.

[0061] (3) Enzyme-catalyzed colorimetric detection of S 2− and CrO4 2− The process S 2− For colorimetric detection, accurately measure 550 μL of the Ti-co-Ce ox@CC-TMB mixed solution prepared in Example 2 and 300.0 μL of S 2− The standard solution and sample solution were placed in a 3.0 mL volumetric flask, made up to 3.0 mL with pure water, left to stand at room temperature for 13 min, and their UV-vis spectra were measured.

[0062] CrO4 2− For colorimetric detection, accurately measure 300 μL of the above Ti-co-Ce ox@CC-TMB mixed solution and 300.0 μL of CrO4 2− The standard solution and sample solution were placed in a 3.0 mL volumetric flask, made up to 3.0 mL with pure water, allowed to stand at room temperature for 5 min, and their UV-vis spectra were measured.

[0063] (4) Catalytic colorimetric detection of S 2− Selectivity Take 550 μL of the above Ti-co-Ce ox@CC-TMB mixed solution and place it in a 3.0 mL volumetric flask. Add 300.0 μL of 1.0×10 −5 mol·L −1 The same concentration of F − , Cl − , Br − , I − , C2O4 2− , Ac − , NO3 − , CN −, SO3 2 − , SO4 2− , ClO3 − , B4O7 2− , SiO3 2− , CO3 2− , Ca 2+ , Co 2+ , citric acid (Cit), acetone (Ace), urea, leucine (Leu), arginine (Arg) standard solution, and then dilute to 3.0 mL with pure water, let it stand at room temperature for 13 min, and measure its UV-vis spectrum. Figure 5 (a) is the UV-visible spectrum of the Ti-co-Ce ox@CC-TMB catalytic system in the presence of common interfering substances. The results show that in the presence of all the above substances, only S 2− The UV-visible spectrum of the Ti-co-Ce ox@CC-TMB system at 652 nm can be quenched. The right side of Figure 5 (a) shows that S 2− The color of the standard solution before and after the reaction fades from blue to colorless.

[0064] On this basis, we further 2− With other interferents (F − , Cl − , Br − , I − , C2O4 2− , Ac − , NO3 − , CN − , SO3 2− , SO4 2− , ClO3 − , B4O7 2− , SiO3 2− , CO3 2− , Ca 2+ , Co 2+ , citric acid (Cit), acetone (Ace), urea, leucine (Leu), arginine (Arg)) were used for the selectivity experiment. Figure 5 (b) shows the common ions and S 2− The absorbance of the Ti-co-Ce ox@CC-TMB catalytic system at 652 nm (A 652 ) Statistical diagram, in which the yellow color represents the A of the system when the interfering ion exists alone 652 , green is the interfering substance and S 2− A of the coexistence system 652 The results show that when S 2− When coexisting with other interferents, A652 The change is very small, within 5% error, which indicates that the coexisting interfering substances have a great influence on the catalytic colorimetric detection of S 2− There is basically no effect. This shows that the Ti-co-Ce ox@CC-TMB system has a 2− With selective subtractive color response.

[0065] (6) Ti-co-Ce ox@CC catalytic colorimetric detection of S 2− Quantitative parameters In order to determine the Ti-co-Ce ox@CC colorimetric detection S 2−- The quantitative analysis parameters (i.e., the linear range, linear relationship equation, and detection limit of the analytical test) are used for subsequent quantitative detection of S 2− The practical application of different concentrations of S 2− Figure 5 (c) shows the catalytic colorimetric detection of S 2− UV-vis spectroscopic titration curve, Figure 5c The S corresponding to the curve from top to bottom in 2− The concentration gradually increased from 0 to 1.0×10 −5 mol·L −1 The results show that with the increase of S 2− With the gradual increase of concentration, the A 652 Figure 5(d) shows the ∆A 652 With c S 2− The linear relationship curve, S 2− The concentration is 8.0×10 −9 ~1.0×10 −5 mol·L −1 Within the range of M, ∆A 652 (A 0 652 -A 652 ) and c S 2− There is a good linear relationship between them, and the linear equations are ∆ A 652 = 2.76 × 10 −3 +6.05×10 −5 c S 2− (R 2 =0.9989), colorimetric detection S 2− The detection limit was 7.8×10 −9 mol·L −1 Ti-co-Ce ox@CC-TMB is an excellent quantitative detection2− Catalytic colorimetric sensor.

[0066] (7) Catalytic colorimetric detection of CrO4 2− Selectivity: Take 300 μL of the above Ti-co-Ce ox@CC-TMB mixed solution and place it in a 3.0 mL volumetric flask, add 300.0 μL of 1.2×10 −5 mol·L −1 The same concentration of 1.2×10 −5 mol·L −1 F − , Cl − Br − ,I − 、C2O4 − ,Ac − 、NO3 − 、NO2 − , CN − 、SO3 2− 、SO4 2− 、P2O7 4− 、ClO3 − 、B4O7 2− 、SiO3 2− IO3 − 、Co 2+ Cr 2+ , glucose (Glu), formaldehyde (Fa), asparagine (Asp), ethylene glycol (Gly), citric acid (Cit) and CrO4 2− The standard solution was then diluted to 3.0 mL with pure water, left to stand at room temperature for 30 min, and its UV-vis spectrum was measured. Figure 6 (a) shows the UV-visible spectrum of the Ti-co-Ce ox@CC-TMB catalytic system in the presence of common interfering substances. The results show that in the presence of all the above substances, only CrO4 2− The UV-visible spectrum of the Ti-co-Ce ox@CC-TMB system at 652 nm can be enhanced. The right side of Figure 6 (a) shows that CrO4 2− The color of the standard solution before and after the reaction changes from light blue to dark blue.

[0067] On this basis, CrO4 2− Selectivity experiments were conducted under the condition of coexistence with other interferents. Figure 6 (b) shows the common ions and CrO4 2− A of the Ti-co-Ce ox@CC-TMB catalytic system 652 Statistical chart, the yellow color in the figure is the A of the system when the interfering ion exists alone 652 (i.e., the absorption intensity value at 652 nm), green represents interfering substances and CrO42− A of the coexistence system 652 The results show that when CrO4 2− When coexisting with other interferents, A 652 The change is very small, within 5% error, which shows that the coexisting interfering substances have an impact on the catalytic colorimetric detection of CrO4 2− There is basically no effect. This shows that the Ti-co-Ce ox@CC-TMB system has a great influence on CrO4 2− With selective hyperchromic response.

[0068] (8) Catalytic colorimetric detection of CrO4 2− Quantitative parameters: To determine the colorimetric detection of CrO4 by Ti-co-Ce ox@CC 2− The quantitative analysis parameters (i.e., the linear range, linear relationship equation, and detection limit of the analysis) are used for the subsequent quantitative detection of CrO4 2− The practical application of the test was based on the different concentrations of CrO4 2− Figure 6 (c) shows the catalytic colorimetric detection of CrO4 2− UV-vis spectroscopic titration curves, the curves in Figure 6 (c), from bottom to top CrO4 2− The concentration increases from 0 to 1.2×10 −5 M, the results show that with the increase of CrO4 2− With the gradual increase of concentration, the A 652 Figure 6 (d) shows the ∆A 652 With c CrO4 2− Linear relationship curve, CrO4 2− The concentration was 2.0×10 −7 ~1.2×10 −5 Within the range of M, ∆A 652 (A 0 652 -A 652 ) and c CrO4 2− There is a good linear relationship between them, and the linear equations are ∆ A 652 =2.70×10 −3 c CrO4 2− −0.0041 (R 2 =0.9988), colorimetric detection of CrO4 2− The detection limit is 5.0×10 −8 mol·L −1Ti-co-Ce ox@CC-TMB is an excellent quantitative detection method for CrO4 2− Catalytic colorimetric sensor.

[0069] (9) Catalytic colorimetric detection of S in actual samples 2− and CrO4 2− Applications According to the experimental steps (4), the Ti-co-Ce ox@CC-TMB system was applied to the catalytic colorimetric detection of S in actual samples. 2− and CrO4 2− , and will not join S 2− and CrO4 2− The absorbance of the system at 652 nm is recorded as A 0 652 ; in S 2− and CrO4 2− The absorbance at that time is recorded as A 652 , calculate the corresponding ∆A 652 (A 0 652 -A 652 )value; When there is a color reduction effect, detect S 2− When ∆A 652 Substituting into the linear regression equation ∆ A 652 = 2.76 × 10 −3 +6.05×10 −5 c S 2− In the calculation, the S 2− concentration; when it has a color enhancement effect, detect CrO4 2− When ∆A 652 Substituting into the linear regression equation ∆ A 652 = 2.76 × 10 −3 +6.05×10 −5 c S 2− The CrO4 in the corresponding sample is calculated. 2− The results are shown in Table 1.

[0070] Table 1. Enzyme-catalyzed colorimetric detection of S in actual samples 2− and CrO4 2− Results (n=5) a Table 1 a The superscript indicates cTi-co-Ce ox@CC =0.34 mg / mL, pH 3.0; b The superscript indicates that the true value of the sample is the measured value in the table × 100; c The superscript indicates that the true value of the sample is the measured value in the table × 5.

[0071] The standard addition method was used to determine S 2− and CrO4 2− As shown in Table 1, the colorimetric detection of S 2− The standard deviations (RSDs) of the samples were all less than 1.88%, and the recoveries were between 197.44% and 104.68%. 2− The standard deviations (RSDs) were all less than 2.33%, and the recoveries were between 97.11% and 104.30%.

[0072] The results showed that the Ti-co-Ce ox@CC simulated oxidase can be used to synthesize S 2− and CrO4 2− The visible colorimetric detection has the characteristics of high sensitivity and accurate detection results.

[0073] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0074] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0075] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A composite material of Ce-Ti bimetallic oxide modified chitosan, characterized in that: The composite material comprises carboxylated chitosan and nano-metal composite oxides loaded on the carboxylated chitosan fibers, wherein the nano-metal composite oxides are coupled with electron-rich N and O groups on the carboxylated chitosan through coordination bonds, and the nano-metal composite oxides comprise nano-cerium dioxide, titanium dioxide and cerium-titanium oxide, and the composite material is formed into the shape of nano-fibers.

2. The composite material according to claim 1, characterized in that The particle size of the nano metal composite oxide is 4.13±0.58 nm.

3. The composite material according to claim 1, characterized in that The molar ratio of carboxylated chitosan, Ce element and Ti element in the composite material is 6-10:7-10:

1.

4. A method for preparing a composite material of Ce-Ti bimetallic oxide modified chitosan according to any one of claims 1 to 3, characterized in that: The preparation method comprises: mixing cerium salt, titanium salt and carboxylated chitosan solution, and then performing reflux reaction under microwave conditions to obtain a composite material of Ce-Ti bimetallic oxide modified chitosan.

5. The preparation method according to claim 4, characterized in that: A pH adjusting agent is also added to the reaction raw materials.

6. The preparation method according to claim 4, characterized in that: The cerium salt is cerium nitrate hexahydrate or cerium sulfate.

7. The preparation method according to claim 4, characterized in that: The conditions for the reflux reaction are: temperature of 100-120°C and reaction time of 10-40 min.

8. Application of a preparation method of a composite material of Ce-Ti bimetallic oxide modified chitosan as described in any one of claims 1 to 3 and a composite material of Ce-Ti bimetallic oxide modified chitosan as described in any one of claims 4 to 7 in nanozymes.

9. A composite material of Ce-Ti bimetallic oxide modified chitosan as claimed in any one of claims 1 to 3 as a nanozyme in S 2− and CrO4 2− Application in detection.

10. An enzyme-mimicking catalytic sensor, characterized in that: The enzyme-mimicking catalytic sensor comprises the composite material of Ce-Ti bimetallic oxide-modified chitosan according to any one of claims 1 to 3.